BIBLICAL ECO-CONCERNS IN THE CONTEXT OF ASIAN RELIGIONS - Pathrapankal, Joseph (Asian Horizons, 2012)
Thousands of years ago a Hebrew poet, looking at the sky, wrote: How clearly the sky reveals God’s glory! How plainly it shows what he has done! Each day announces it to the following day; each night repeats it to the next. No speech or words are used, no sound is heard. Yet their message goes out to the entire world and is heard to the ends of the earth. God made a home in the sky for the sun; it comes out in the morning like a happy bridegroom, like an athlete eager to run a race. It starts at one end of the sky and goes across to the other (Ps 19:1-6).